Corona Effect in Frequency Dependent Transmission Line Models - Freitas, M. A.; Kurokawa, S. [UNESP]; Pissolato, J.; IEEE (Ieee, 2008)
The inclusion of the corona effect in a frequency dependent transmission line model is proposed in this paper. The transmission line is represented through a cascade of pi circuits and the frequency dependence of the longitudinal parameters is synthesized with series and parallel resistors and inductors. The corona effect will be represented using the Gary and Skilling-Umoto models. The currents and voltages along the line are calculated by using state-space technique. To demonstrate the accuracy and validity of the proposed frequency dependent tine model, time domain simulations of a 10 km length single-phase line response under energization procedure will be presented.
Keywords: transmission lines; time domain analysis; state space methods; corona